Chemico‐mechanical imaging of Barrett's oesophagus. Issue 7 (18th April 2016) - Palombo, Francesca; Madami, Marco; Fioretto, Daniele; Nallala, Jayakrupakar; Barr, Hugh; David, Antoine; Stone, Nick
Abstract : Barrett's oesophagus is a condition characterized by a change in the lining of the oesophagus that markedly increases the risk of adenocarcinoma. We demonstrate the first site‐matched application of Brillouin microscopy, Raman microscopy and FTIR micro‐spectroscopic imaging to ex‐vivo epithelial tissue – Barrett's oesophagus. The mechanical and chemical characters of the epithelium were assessed in histological sections from a patient subjected to endoscopic oesophageal biopsy. Previous studies have shown that both these properties change within the oesophageal wall, owing to the presence of distinct cellular and extracellular constituents which are putatively affected by oesophageal cancer. Brillouin microscopy enables maps of elasticity of the epithelium to be obtained, whilst Raman and FTIR imaging provide 'chemical images' without the need for labelling or staining. This site‐matched approach provides a valuable platform for investigating the structure, biomechanics and composition of complex heterogeneous systems. A combined Brillouin‐Raman device has potential for in‐vivo diagnosis of pathology.First application of site‐matched micro Brillouin, Raman and FTIR spectroscopic imaging to epithelial tissue in Barrett's oesophagus Abstract : Barrett's oesophagus is a condition characterized by a change in the lining of the oesophagus that markedly increases the risk of adenocarcinoma. Here, the first site‐matched application of Brillouin microscopy, Raman microscopy and FTIR micro‐spectroscopic imaging to ex‐vivo epithelial tissue – Barrett's oesophagus is demonstrated. Brillouin microscopy enables maps of elasticity of the epithelium to be obtained, whilst Raman and FTIR imaging provide 'chemical images' without the need for labelling or staining. This approach provides a valuable platform for investigating the structure, biomechanics and composition of complex heterogeneous systems.